PROBLEM BASED LEARNING APPROACH WITH SCIENCE KIT SEQIP TO ENHANCING STUDENTS’ SCIENTIFIC PROCESS SKILLS AND COGNITIVE LEARNING OUTCOMES - Erwinsyah Satria (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This classroom action research was motivated by the students’ low scientific process skills and cognitive learning outcomes in natural science. One of the reasons is the lack of teachers’ ability in choosing appropriate learning model and using of Kit or learning science equipments in natural science learning. Thus, the implementation of Problem Based Learning approach with science Kit Seqip to students of class V SDN 20 Kurao Pagang Padang is one of the ways to solve this problem. The objective of this research is to describe the improvement of the students’ scientific process skills and cognitive learning outcomes in natural science at class V at SDN 20 Kurao Pagang Padang by using Problem Based Learning approach with science Kit Seqip. The instruments of this research were the observation sheets of students’ scientific process skills and teachers’ activities and the test sheets of students’ cognitive learning outcome. The results showed that there was a significant improvement of students’ scientific process skills and cognitive learning outcomes in natural science class V by using Problem Based Learning approach with science Kit Seqip from the first cycle to the second cycle